JENIS DAN PROSES PEMBENTUKAN ADJEKTIVA WARNA DALAM BAHASA MINANGKABAU DI KENAGARIAN TAEH BARUAH KABUPATEN LIMA PULUH KOTA - Amaral, Winda; Juita, Novia (Universitas Negeri Padang, 2019)
This study aims to: (1) describe the type of color adjectives, (2) describe the process of forming color adjectives in the Minangkabau language in Kenagarian Taeh Baruah district Lima Puluh Kota. This type of research is qualitative research using descriptive methods. First, the type of color adjectives in the Minangkabau language in Kenagarian Taeh Baruah regency Lima Puluh Kota are as follows: (1) based on animal names, (2) based on plant names, (3) based on natural objects, (4) based on vision, (5) based on limbs, (6) based on food. Second, there are two processes for the formation of color adjectives in the Minangkabau language, namely (1) basic adjectives, and (2) derivative adjectives (compound words).Â Â Keyword:Type, Process of Formation, Adjectives, Minangkabau Language.Â